After Ever Happy - Todd, Anna (New York Gallery Books, 2015)
"Tessa and Hardin have had enough surprises. Their bond is stronger than ever, but every new challenge they face shakes their foundation--and Hardin's impenetrable façade--to the core. As the shocking truth about each of their families emerges, it's clear the two lovers are not so different from each other. Tessa is no longer the sweet, simple, good girl she was when she met Hardin--any more than he is the cruel, moody boy she fell so hard for. Tessa understands all the troubling emotions brewing within Hardin, and she knows she's the only one who can calm him when he erupts. He needs her. But the more layers of his past that come to light, the darker he grows, and the harder he pushes Tessa--and everyone else in his life--away. After all this time, Tessa's not sure if she really can save him--not without sacrificing herself. Is love worth losing her identity? She refuses to go down without a fight. But who is she really fighting for--Hardin or herself?"
Keywords: College students -- College stories -- Man-woman relationships